Kinematic synthesis and simulation of a vegetable pot seedling transplanting mechanism with four exact task posesKinematic synthesis and simulation of a vegetable pot seedling transplanting mechanism with four exact task poses - Sun, Liang; Xu, Haocong; Zhou, Yuzhu; Shen, Jiahao; Yu, Gaohong; Hu, Huafeng; Miao, Yuejun (International Journal of Agricultural and Biological Engineering, 2023)
To obtain a picking and planting integrated transplanting mechanism (PITM) with ideal trajectory shape, reasonable operating attitude, and compact structure for vegetable pot seedling transplanting, a symmetrical structural PITM composed of two planetary carriers and driven by a cam–noncircular gear combination mechanism was proposed in this paper. In accordance with the requirements of transplanting agronomy, the shape of the motion trajectory and the attitude of the end tip of the clamping claw at several specific positions (the starting and end points of picking seedling, the starting point of pushing seedling, and a special point on the return segment) were planned. To make the clamping claws of PITM pass through a set of prescribed positions, the mechanism was simplified to an open-chain 3R mechanism. An accurate four-position-based method for solving the open-chain mechanism model was adopted to obtain the curves of its fixed hinge point (central point) and dynamic hinge point (circle point). The ratio of adjacent bars’ lengths was analyzed to determine the feasible interval of the central and circle point curves and the reasonable link length. A desired closed transplanting trajectory that goes through the given points and the corresponding transmission ratio model of the open-chain mechanism was established. After the transmission ratio of each stage of gear and cam pairs was calculated and distributed, the prototype of PITM was designed and manufactured. Lastly, the effectiveness and feasibility of the design were verified through a preliminary experiment of the prototype.Keywords: kinematic synthesis, transmission ratio, non-circular gear, planetary carrierDOI: 10.25165/j.ijabe.20231602.6739Citation: Sun L, Xu H C, Zhou Y Z, Shen J H, Yu G H, Hu H F, et al. Kinematic synthesis and simulation of a vegetable pot seedling transplanting mechanism with four exact task poses. Int J Agric & Biol Eng, 2023; 16(2): 85-95.